"We're like community": Collective identity and collective efficacy among transgender women in prisons for men. (December 2016) - Sexton, Lori; Jenness, Valerie
Recognizing that prisons house diverse populations in equally diverse types of environments, we utilize a unique data set and employ two well-known sociological concepts—collective identity and collective efficacy—to examine overlapping communities in which transgender women in prisons for men are situated and experience prison life. Findings from our mixed-methods analysis reveal that despite their considerable diversity, transgender prisoners embrace a collective identity and perceive collective efficacy as transgender prisoners more so than as prisoners per se ; their collective identity and perceptions of collective efficacy are predicated on social-interactional factors rather than demographic characteristics and physical features of the carceral environment; and the more time a transgender inmate spends in prison, the more likely she is to identify with a community of transgender prisoners, but the less likely she is to feel an affective commitment to the transgender prisoner community or to expect other transgender prisoners to act on her behalf in prison. This novel application of dynamics generally understood to operate in social movements and residential neighborhoods—collective identity and collective efficacy, respectively—to the transgender community in California's prisons sheds insight into the ways in which transgender women in prisons for men experience prison life, the loyalties around which prison life is organized, and the complexities around which communities in prison are structured.